Genomic Profiling Identified Novel Prognostic Biomarkers in Chinese Midline Glioma Patients - Li, Hainan; Shan, Changguo; Wu, Shengnan; Cheng, Baijie; Fan, Chongzu; Cai, Linbo; Chen, Yedan; Shi, Yuqian; Liu, Kaihua; Shao, Yang; Zhu, Dan; Li, Zhi (Frontiers in Oncology, 2021)
Background: Molecular characteristics are essential for the classification and grading of gliomas. However, diagnostic classification of midline glioma is still debatable and substantial molecular and clinical heterogeneity within each subgroup suggested that they should be further stratified. Here, we studied the mutation landscape of Chinese midline glioma patients in hope to provide new insights for glioma prognosis and treatment. Methods: Tissue samples from 112 midline glioma patients underwent next-generation sequencing targeting 425 cancer-relevant genes. Gene mutations and copy number variations were investigated for their prognostic effect using overall survival data. Pathway-based survival analysis was performed for ten canonical oncogenic pathways. Results: We identified several currently established diagnostic and prognostic biomarkers of glioma, including TP53 (33%), EGFR (26%), TERT (24%), PTEN (21%), PIK3CA (14%), ATRX (14%), BRAF (13%) and IDH1/2 (6%). Among all genetic aberrations with more than 5% occurrence rate, six mutations and three copy number gains were greatly associated with poor overall survival (univariate, P<0.1). Of these, TERT mutations (hazard ratio [HR], 3.00; 95% confidence interval [CI], 1.37-6.61; P=0.01) and PIK3CA mutations (HR, 2.04; 95% CI, 1.08-3.84; P=0.02) remained significant in multivariate analyses. Additionally, we have also identified a novel MCL1 amplification (found in 31% patients) as a potential independent biomarker for glioma (multivariate HR, 2.78; 95% CI, 1.53-5.08; P<0.001), which was seldom reported in public databases. Pathway analyses revealed significantly worse prognosis with abnormal PI3K (HR, 1.81; 95% CI, 1.12-2.95; P=0.01) and cell cycle pathways (HR, 1.97; 95% CI, 1.15-3.37; P=0.01), both of which stayed meaningful after multivariate adjustment. Conclusions: In this study, we discovered shorter survival in midline glioma patients with PIK3CA and TERT mutations and with abnormal PI3K and cell cycle pathways. We also revealed a novel prognostic marker, MCL1 amplification that collectively provided new insights and opportunities in understanding and treating midline gliomas.